Hot electron generation and transport using Kα emission - Akli, K; Stephens, R; Key, M; Bartal, T; Beg, F; Chawla, S; Chen, C; Fedosejevs, R; Freeman, R; Friesen, H; Giraldez, E; Green, J; et al. (2010)
We have conducted experiments on both the Vulcan and Titan laser facilities to study hot electron generation and transport in the context of fast ignition. Cu wires attached to Al cones were used to investigate the effect on coupling efficiency of plasma surround and the pre-formed plasma inside the cone. We found that with thin cones 15% of laser energy is coupled to the 40μm diameter wire emulating a 40μm fast ignition spot. Thick cone walls, simulating plasma in fast ignition, reduce coupling by x4. An increase of pre-pulse level inside the cone by a factor of 50 reduces coupling by a factor of 3. © 2010 IOP Publishing Ltd.